2020
DOI: 10.18009/jcer.649547
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Views on Parent Involvement for Refugee Children’s Education

Abstract: Wars, with their exhaustively long effects, cause people leave their countries and become refugees. Children are those who are affected most due to this situation. Undoubtedly, education is one of the basic rights of refugee children. Active and efficient family involvement is crucial to achieve the sufficient level in education. In this context, the aim of this study is to determine the level of parent involvement of refugee children. The study is designed as a phenomenological research. To this end, semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
1
3
0
3
Order By: Relevance
“…Mace, Mulheron, Jones and Cherian (2014) found that economic problems and language barriers were the reasons parents were indifferent to school. The problems that administrators have with parents are mostly problems caused by parents' long working periods, due to financial difficulties, students are not adequately cared for, some parents cannot support children because they are illiterate, so attendance at parent meetings is low (Sönmez, 2018;Zengin, Ataş-Akdemir, 2020). Kultas, (2016) has produced similar results in its research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mace, Mulheron, Jones and Cherian (2014) found that economic problems and language barriers were the reasons parents were indifferent to school. The problems that administrators have with parents are mostly problems caused by parents' long working periods, due to financial difficulties, students are not adequately cared for, some parents cannot support children because they are illiterate, so attendance at parent meetings is low (Sönmez, 2018;Zengin, Ataş-Akdemir, 2020). Kultas, (2016) has produced similar results in its research.…”
Section: Discussionmentioning
confidence: 98%
“…Otherwise, many problematic behaviors such as violence, bullying, sexual abuse may occur. In this regard, family-related studies are listed as promoting cultural beliefs, maintaining cultural life, education for children and employment for adults in order to facilitate family harmony (Fazel, Reed, Panther Brick & Stein, 2012;Zengin, Ataş-Akdemir, 2020). Carrying out studies on the development of peer relations with children within the school, organizing activities can be considered as factors that facilitate their adaptation.…”
Section: Immigration and Its Effect On Educationmentioning
confidence: 99%
“…Hâlbuki öğretmenlerin velilerle işbirliği ve iletişim içinde olması öğrencilerin uyumsuz davranışlarının altında yatan nedenlerin bulunmasında faydalı olacaktır (Alidou, 2000). Buna karşın ebeveynlerin Türkçe konuşamamaları, Türkiye'deki durumu geçici olarak algılamaları gibi nedenlerle mülteci öğrenciler için ebeveyn katılımı ve işbirliği düşük düzeyde kalabilmektedir (Zengin ve Ataş-Akdemir, 2020). Dolayısıyla öğretmenler, mülteci öğrencilerin aile katılımını artırmada, iletişim ve işbirliğini geliştirmede etkili stratejiler geliştirebilmeli ve eğitim ortamlarını buna göre çeşitlendirebilmelidir.…”
Section: Discussionunclassified
“…Son yıllarda Türkiye'de yürütülen çalışmalarda Suriyeli göç mağduru çocukların eğitim sürecinde yaşadıkları sorunlara ve bu sorunlara yönelik çözüm önerilerine ilişkin çok sayıda çalışma yürütülmüştür (bkz. Akpınar, 2017;Aydin & Kaya, 2017;Başar, Akan & Çiftçi, 2018;Emin, 2016;Erçetin & Kubilay, 2018;Erçetin, Potas & Açıkalın, 2017;Ertaş & Çiftçi Kıraç, 2017;Hauber-Özer, 2019;Kazu & Deniz, 2019;Seydi, 2014;Şentürk, 2018;Zengin & Ataş-Akdemir, 2020). Salgın öncesi dönemde ön plana çıkan bu sorunların daha çok dil ve iletişim sorunları olduğu ayrıca bu çocukların yaşadığı yoksunluk, şiddet ve ölüm olaylarının yarattığı travmaların etkisiyle psiko-sosyal sorunlar ve uyum sorunları yaşadıkları tespit edilmiştir.…”
Section: Introductionunclassified